(untitled) (Journal of Environmental Science and Natural Resources, 2022)
The study was conducted to investigate the concentration of PM2.5, PM10, CH4, CO2, CO, SO2 in the air of Tangail Sadar Upazila, Tangail. In the study area air quality data has been collected from eight sampling stations namely MBSTU campus, Baby stand, Nirala more, New bus stand, Rabna bypass, College gate, Old bus stand, Nogor jalfoi during dry season. The air quality data collected by using Aeroqual S 500 series. The concentrations of PM2.5, PM10, CH4, CO2, CO, SO2 found in air were ranged from 0.03-0.06, 0.04-0.10, 12.3-36, 919-1238.2, 0.00- 2.61, 0.00-0.48 mg/m3, respectively. The concentration of PM2.5, PM10, CO, SO2 that have been found were higher than Bangladesh standard and WHO guideline. Their sources could be the motor vehicles, road dust, coal burning, road construction, open dumping of solid waste in Tangail Sadar Upazila. Appropriate engine design control strategies and maintenance services should be introduced for reducing emission. Efficient solid waste management system should be introduced to control emission from construction sources. Environ. Sci. & Natural Resources, 13(1&2): 118-122, 2020